271 DEVELOPMENT OF AN INNOVATIVE INTER-DISCIPLINARY PARKINSON'S CLINIC IN AN AMBULATORY CARE SETTING. (25th October 2022) - Kimmage, E; Carney, C; Conaty, S; Cronin, A; Digan, E; Kennelly, SP; McDonagh, A; McWilliams, O; Nolan, E; O'Dwyer, A; O'Rourke, L; Pierpoint, R; et al.
Abstract: Background: Ambulatory services provide specialist outpatient care, reducing costs associated with inpatient admissions and enabling the person to remain at home for longer (Report of the National Acute Medicine Programme, 2010). An Older Person's Ambulatory Care Hub was established in a large teaching hospital. Prior service evaluation demonstrated that approximately one third of patients attending had a diagnosis of Parkinson's Disease (PD). People with PD should have a collaborative approach between patient, family and healthcare providers to optimally manage their condition (NICE, 2017), therefore, the need was identified to evolve the traditional medical model to an interdisciplinary approach. The aim of this project was to complete a service evaluation and breakdown of Interdisciplinary Team (IDT) referrals. Methods: An IDT working group including Clinical Nutrition (CN), Medical, Nursing, Occupational Therapy (OT), Physiotherapy (PT), and Speech and Language Therapy (SLT) was established. A comprehensive assessment form was developed and outcome measures were chosen. A short pilot was conducted and necessary amendments were made. A weekly clinic was established which included an IDT assessment, followed by a huddle with the medical team where referrals were generated. Data pertaining to the number of attendees and referrals generated were collected over a 3-month period. Results: Over the data collection period, 31 patients attended the clinic. Referrals were as follows; Medical: 19, PT: 13, SLT: 10, OT: 7, CN: 6, Medical Social Work: 2. Patients requiring urgent medical review were seen immediately after the IDT huddle. Conclusion: This project demonstrates a service evaluation of a novel IDT PD Clinic. This clinic highlights the need for an IDT approach to management of people with PD. Future service developments include obtaining patient feedback, pre-clinic calls to patients by a Healthcare Assistant to explain the purpose of the clinic, and adapting the clinic as appropriate.